Sejarah Pemikiran dan Gerakan Pembaharuan Islam di Indonesia: Sebuah Kajian Historis - Suci Urmilawati; Zainuddin Syarif (Kartika: Jurnal Studi Keislaman, 2026)
This article examines the history of Islamic thought and reform movements in Indonesia by tracing the development of Islam from its early arrival to the contemporary period. The study aims to identify the transformation of Islamic intellectual discourse and the dynamics of reform movements that emerged in response to social change, colonial pressures, modernization, and globalization. The research employs a historical approach based on literature review, archival documents, and the analysis of reformist scholars’ ideas. The findings indicate that Islam entered the Indonesian archipelago peacefully through trade routes around the 7th century and expanded significantly in the 13th century, leading to the establishment of Islamic kingdoms and the growth of religious scholarship. In the modern era, prominent reformers such as Hasyim Asy’ari, Ahmad Dahlan, and Abdurrahman Wahid introduced integrative concepts related to Islam, education, pluralism, and democracy. This study concludes that Islamic reform in Indonesia is a continuous and dynamic process that seeks to maintain the relevance of Islamic teachings in social and national life.